Pengembangan Website WardellTech dengan Agile Scrum dan Laravel untuk Mendukung Layanan Freelance - Syah Bintang; Rangga Wasita Ningrat; Jonathan Cristiano Rabika; Mochammad Alwan Al Ataya; Aditya Wicaksono; Mindra, Gema Parasti (Universitas Boyolali, 2025)
This research focuses on the development of a freelance e-commerce website for WardellTech using the Laravel framework. The objective is to build a web-based platform that is secure, responsive, and user-friendly, supporting freelance service transactions. Laravel was selected for its structured MVC architecture, built-in security features, and its ability to streamline development and maintenance. A Software Requirements Specification (SRS) document was created to define both functional and non-functional requirements in detail, ensuring that all stakeholders—developers, testers, and project managers—have a unified understanding of the system. WardellTech specializes in web and mobile application development, emphasizing quality design, user experience, and data security. Therefore, the website integrates key features such as secure payment gateways, intuitive navigation, and optimized performance. Continuous analysis and improvement of the user interface are also prioritized to enhance usability and customer satisfaction. The final system is expected to not only meet WardellTech’s business needs but also compete effectively in the freelance digital services market. Additionally, it is designed to adapt to ongoing technological advancements and evolving user demands in the dynamic e-commerce landscape.